The Role of Specular Reflections and Illumination in the Perception of Thickness in Solid Transparent Objects - Ohara, Masakazu; Kim, Juno; Koida, Kowa (Frontiers in Psychology, 2022)
Specular reflections and refractive distortions are complex image properties of solid transparent objects, but despite this complexity, we readily perceive the 3D shapes of these objects (e.g., glass, clear plastic). We have found in past work that relevant sources of complexity have differential effects on 3D shape perception, with specular reflections increasing perceived thickness and refractive distortions decreasing perceived thickness. In an object with both elements, such as glass, the two optical properties may complement each other to support reliable perception of 3D shape. We investigated the relative dominance of specular reflection and refractive distortions to the perception of shape. Surprisingly, the ratio of specular reflection to refractive component was almost equal to that of ordinary glass and ice, which promote correct percepts of 3D shape. The results were also explained by the variance in local RMS contrast in stimulus images but may depend on overall luminance and contrast of the surrounding light field.